INTERNALISASI NILAI PANCASILA DALAM PEMBENTUKAN KARAKTER MAHASISWA DI PERGURUAN TINGGI - Camelia, Happy Gisella; Aila Azzura; Aura Lentera Qolbi; Marcelina Angel Wahyudiyanti; Anggun Novita Sari; Kusnul Khotimah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The purpose of this research is to determine how Pancasila is internalized in the character formation of students in higher education and how effectively these principles are applied today. This study, using a quantitative approach, utilized a descriptive survey involving 61 active undergraduate students in Indonesia who were purposively selected. Data were collected using a questionnaire-based tool and then analyzed using a descriptive survey. The study showed that the majority of students believe Pancasila is crucial for building their character. The results showed that 98.4 percent of respondents stated that Pancasila education is important for professional development, and 96.7 percent stated that Pancasila education should be studied scientifically. However, there are still significant differences in how people understand and apply Pancasila in their daily academic lives. This indicates that the process of internalizing values is still inefficient and predominantly cognitive. This study suggests that incorporating Pancasila values into the lives of students in higher education requires a more holistic approach.